Discovery of substituted 1, 4-dihydroquinolines as novel class of ABCB1 modulators. Issue 15 (1st August 2015) - Hemmer, Marc; Krawczyk, Sören; Simon, Ina; Lage, Hermann; Hilgeroth, Andreas
Graphical abstract: Abstract: Transmembrane efflux pumps are one main cause for multidrug resistance (mdr) of cancer. One hopeful approach to combate the mdr has been the development of inhibitors of the efflux pump activity. A novel class of small-molecule inhibitors of the most important efflux pump ABCB1 (P-glycoprotein) has been discovered. Inhibitory activities are discussed in relation to substituent effects. Most active compounds have been evaluated in first bioanalytical studies to reverse the mdr of an anticancer drug. Cellular toxicity and ABCB1 substrate properties of the compounds were investigated. A cellular induction of relevant efflux pump protein expressions was not observed under inhibitor application, so that our compounds are perspective candidates for further preclinical studies.